Analisis Pengaruh PDRB Perkapita, Upah Minimum, Penyerapan Tenaga Kerja, Jumlah Penduduk Miskin Terhadap Indeks Pembangunan Manusia di Propinsi Jawa Barat Tahun 2017-2020 - Rian Hidayat, Wasi Nuroso; Perwithosuci, Winny (UNIVERSITAS MUHAMMADIYAH SUMATERA UTARA, 2024)
HDI is one of the determining factors reflecting a decent life. HDI makes one of the Keys where economic growth increases with the quality of human resources in the country. West Java province is one of the provinces that has a fairly high HDI value each year. This study aims to determine the effect, GDP per capita, minimum wage employment, the number of poor people on Human Development Index (HDI) in West Java province. This study is a quantitative research and the data used in this study are secondary data obtained from the Central Statistics Agency, the analysis used is a panel data regression in the form of Cross Section 27 districts in West Java province in 2017-2020 . Based on the results of panel data regression analysis can be explained that the selected model is a Fixed Effect Model or ( FEM ). The results of the GDP model estimation have a positive effect on HDI, the workforce has a positive effect on HDI. Minimum wage has a positive effect on HDI. Labor has no positive effect on HDI, the number of poor people has no positive effect on HDI. Test F with prob 0.0000 and R-square of 0.9968 or 99.68%.